PENGARUH PENGUNGKAPAN PENGUKURAN KINERJA NONFINANSIAL TERHADAP MANAJEMEN LABA DENGAN LEVERAGE, PROFITABILITAS DAN UKURAN PERUSAHAAN SEBAGAI VARIABEL PEMODERASI (STUDI KASUS PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2015) - Purnami, Ayu; Kuntaryanto, Oki (KIAT BISNIS, 2016)
The purpose of this research is to examine the influence of disclosure of nonfinancial performance measurement to earnings management with leverage, profitability and firm size as the moderating variable in manufacturing companies listed at Indonesia Stock Exchange period 2015. The populations in this research are manufacturing companies listed at Indonesia Stock Exchange for the 2015 financial year and purposive sampling is used as sampling method. Sample in this research is 82 manufacturing companies and the hypothesis test is performed by using simple linier regression and the absolute value of the difference test with software SPSS for Windows versi 16.0. The result of this research indicates that the disclosure of nonfinancial performance measurement has significant influence to earnings management. But leverage, profitability and firm size as the moderating variable can not influence the relation disclosure of nonfinancial performance measurement to earnings management. Keyword: disclosure of nonfinancial performance measurement, leverage, profitability, firm size, and earnings management